Politics of Education in Nigeria: Government Influence and Its Implications - Ugwu, Vitalis Ikechukwu (Papanda Publishier, 2025)
There has been an inseparable link between politics and education in the society. The fact that politics and government decisions can affect all aspects of society has closely linked education to politics. Government policies and political decisions regulate nearly everything that happens in the society including education. Adopting qualitative document analysis design and anchored on Political Economy of Education Theory, this article explores how politics and government influence education and its implication on the structure and quality of education delivery in Nigeria from colonial period to date. Specifically, this article addresses the following research questions: (i) In what ways do politics and government influence the structure and delivery of education in Nigeria? (ii) What are the implications of influence of politics and government on Nigerian educational system? Based on data from secondary sources such as books, journal articles, and newspapers, the findings of this study show that politics and government influence the educational system through funding, policy formulation and implementation, appointment of educational leaders, curriculum development and implementation, and admission policies, among others. The implication of government influence is that when the government does not handle well any of the means through which they influence education, it will affect negatively the standard and quality of education in Nigeria. All the stakeholders in education and the general public need to understand the relationship between the government and education. The knowledge will enable the stakeholders to support the government in making policies that will promote quality education.